Prevalence of anaemia in pregnancy in the Uthungulu health district of KwaZulu-Natal, South Africa - Monjurul Hoque; Suriya B. Kader; Ehsanul Hoque (South African Family Practice)
Background: An estimated 30% of the world's population is affected with anaemia. Anaemia in pregnancy is a leading cause of maternal and perinatal deaths in developing countries. In developing countries, anaemia affects almost two thirds of the pregnant population. It is also estimated that anaemia is responsible for as much as 20% of all maternal deaths in sub-Saharan Africa. Maternal anaemia is a risk factor for infant iron deficiency anaemia and, if left uncorrected, can be associated with adverse behavioural and cognitive development in children. The prevalence of anaemia in pregnancy is estimated at between 35% and 75% in sub-Saharan Africa, however, the area-specific health problems during pregnancy are not known. In order to improve maternal health and the health of the foetus during pregnancy, knowledge of the prevalence or incidence of pregnancy-related conditions would be useful for district management teams, as well as for provincial and national maternal, child and women's health programme development. The objectives of this study were to describe haemoglobin levels and estimate the prevalence of anaemia among pregnant women at their booking visit.